2016
DOI: 10.1007/s10144-016-0536-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of faeces counts to estimate relative densities of wild boar in a Mediterranean area

Abstract: The monitoring of population trends of wild ungulates is important to evaluate their population dynamics and to develop sound conservation/management plans. The wild boar Sus scrofa can impose heavy impacts on ecosytems and human activities, as well as be responsible for disease transmission. Estimating abundance of wild boars is a challenging issue, because of some peculiar biological and ecological traits of this ungulate. Indices of relative abundance could be used to evaluate its population trends. In a Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…Several methods have been developed and applied to determine relative densities or population indices of wild boar. These methods include hunting statistics, pellet counts and activity signs, capture–mark–recapture based on faecal DNA or on marked animals, and distance sampling . The advantages, disadvantages and reliability of each of these methods have been widely discussed .…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed and applied to determine relative densities or population indices of wild boar. These methods include hunting statistics, pellet counts and activity signs, capture–mark–recapture based on faecal DNA or on marked animals, and distance sampling . The advantages, disadvantages and reliability of each of these methods have been widely discussed .…”
Section: Introductionmentioning
confidence: 99%
“…Following the need of crossborder management (Linnell et al 2020), recent initiatives develop abundance models using hunting statistics at the European scale (ENETWILD-consortium et al 2019). Hunting bags, however, may not be reliable if the hunting effort of a species is not related to its density and when this relationship changes over time (Imperio et al 2010;Willebrand et al 2011;Ferretti et al 2016;Eriksen et al 2018). This may be particularly true for expanding species that occur at low densities or species that are not (yet) part of the mainstream monitoring and ungulate management.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are used for wild boar (Massei et al 1998, Ferretti et al 2014, Plhal et al 2014, Ferretti et al 2016). There are lots of methods based on counting the number of pellets or their frequency along transects or in plots.…”
Section: Pellet Countsmentioning
confidence: 99%
“…There are lots of methods based on counting the number of pellets or their frequency along transects or in plots. Some of them are used for wild boar (Massei et al 1998, Ferretti et al 2014, Plhal et al 2014, Ferretti et al 2016 The present document has been produced and adopted by the bodies identified above as author(s). This task has been carried out exclusively by the author(s) in the context of a contract between the European Food Safety Authority and the author(s), awarded following a tender procedure.…”
Section: Pellet Countsmentioning
confidence: 99%